2008
DOI: 10.1002/jts.20345
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptoms, PTSD, and risk factors among lower Manhattan residents 2–3 years after the September 11, 2001 terrorist attacks

Abstract: Manhattan residents living near the World Trade Center may have been particularly vulnerable to posttraumatic stress disorder (PTSD) after the September 11, 2001 (9/11) terrorist attacks. In 2003-2004, the authors administered the PTSD Checklist to 11,037 adults who lived south of Canal Street in New York City on 9/11. The prevalence of probable PTSD was 12.6% and associated with older age, female gender, Hispanic ethnicity, low education and income, and divorce. Injury, witnessing horror, and dust cloud expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(152 citation statements)
references
References 39 publications
(36 reference statements)
10
140
1
1
Order By: Relevance
“…Although gender ratio, age structure and survey time after a disaster is different, those percentages are almost equal to 20.1% reported in the previous study concerning the rescue and cleanup workers after the 9.11 World Trade Center Attacks 23) . Furthermore, Our results are comparable to those og the previous research in that, L. DiGrande et al showed that the prevalence of probable PTSD using the DSM -IV diagnostic criteria (16.1%) was similar to the prevalence based on the PCL cutoff score 44 or < (15.1%) among lower Manhattan residents 2 -3 years after the September 11, 2001 terrorist attacks 24) . The proportion above PCL cutoff (≥44) was higher among females than males.…”
Section: Discussionsupporting
confidence: 89%
“…Although gender ratio, age structure and survey time after a disaster is different, those percentages are almost equal to 20.1% reported in the previous study concerning the rescue and cleanup workers after the 9.11 World Trade Center Attacks 23) . Furthermore, Our results are comparable to those og the previous research in that, L. DiGrande et al showed that the prevalence of probable PTSD using the DSM -IV diagnostic criteria (16.1%) was similar to the prevalence based on the PCL cutoff score 44 or < (15.1%) among lower Manhattan residents 2 -3 years after the September 11, 2001 terrorist attacks 24) . The proportion above PCL cutoff (≥44) was higher among females than males.…”
Section: Discussionsupporting
confidence: 89%
“…En sık görülen başa çık-ma mekanizması kişinin yakınları ile ilgili bilgi arayı-şı ve sosyal destek olarak görülüyordu. New York'ta 2001 yılı ikiz kuleler saldırısından iki yıl sonra bölge-de genel popülasyonda yapılan bir tarama olası TSSB sıklığını %12,6 olarak bildiriyordu (13) . İleri yaş, kadın cinsiyet, hispanik kökenli olma ve düşük gelir ve eği-tim düzeyi risk etkenleri olarak görünüyordu.…”
Section: Terör Ve Savaş: Epidemiyolojik çAlışmalarunclassified
“…We used the dual criteria to obtain a more conservative estimate of probable PTSD. 11 We have used "PTSD" to denote probable PTSD determined as described. Reported exposures Exposures included being caught in the dust cloud and returning to dustcontaminated homes or workplaces, measures previously linked to both post-9/11 asthma and PTSD.…”
Section: Study Variablesmentioning
confidence: 99%